Determinants of e-learning adoption in higher education in Iraq an academics and students’ perspective - Soreen Ameen Fattah; Ayad Hameed Mousa; Mowafak K. Mohsen; Shahad Dakhil Khalaf; Seham Hameed Mousa (Universitas Ahmad Dahlan, 2022)
E-learning allows the students to access, repeat and use the scientific materials wherever and whenever the users want. Both academics and learners are the leading and essential actors in the process of the learning process. Moreover, the acceptance of a technology is the positive react for users by using such technology. Due to the COVID-19 pandemic, e-learning has become mandatory over the world, thus, there is a necessity to investigate the determinants of e-learning adoption in higher education institutions (HEIs) in Iraq. Consequently, this paper aims to investigate elearning adoption and identify the determinants of e-learning in HEIs. An instrument was developed with eight dimensions based on technology organization and environmental (TOE) elements. The sample selection was of 580 students and 130 university lecturers who spread over several colleges. A clustering sampling method was used in the sampling selection process. Some hypotheses were proposed and tested via the paired T-test tool. To evaluate the relationship between the TOE variables and e-learning adoption, a regression analysis was carried out. The study findings classified into two categories, first, it helps to determine to what extent e-learning be adopted. Second, it provides meaningful guidance for higher education institutions that should follow as a pre-requested before adopting e-learning